Wake Island Wildcat a Marine fighter pilot's epic battle at the beginning of World War II - Ramsey, William L. (Stackpole Books, 2024)
"Wake Island Wildcat tells the story of "Hammerin' Hank," Henry Elrod, the fighter pilot who was the linchpin of the defense of Wake Island, attacked by the Japanese on the same day as Pearl Harbor. This is not only the story of the battle for Wake Island, but also the story of a Marine fighter pilot at war, told with drama and verve"--
Keywords: Kampfflieger; F4F Wildcat; Wake Island -- Schlacht -- 1941; USA; Elrod, Henry Talmage / 1905-1941; Wake Island, Battle of, Wake Island, 1941; Fighter pilots / United States / Biography; United States / Marine Fighter Squadron, 211th / Biography; World War, 1939-1945 / Aerial operations, American; Wildcat (Fighter plane); United States / Marine Corps / Aviation / Biography